Nonverbal Codes in Interpersonal Communication Between Genders of Japanese Native Speakers - Komara Mulya; Dwi Astuti Retno Lestari (Universitas Negeri Semarang, 2023)
This study aims to describe the response when male and female speakers of the Japanese language perform interpersonal communication, which is indicated by conflict by looking at the nonverbal codes and the nonverbal functions used by the threatened communicant. The reason for choosing this topic is that men and women often experience miscommunication when communicating interpersonally, which causes conflicts between men and women. Understanding each other's nonverbal codes shown by each communicator is a way to establish better intergender communication. The theory used is the theory of 3F (freeze, flight, and fight) from Navarro & Karlins (2008) and the theory of nonverbal functions from Ekman and Friesen (1969). The data collection technique used in this study is the note-taking technique and analyzed using a pragmatic equivalent technique. The results of this study show that men who feel threatened by women more often use the fight response, while women who are threatened use the freeze response more often. Men use 16 gestures, while women use 34 when they feel threatened. Looking at the other person is men's and women's most frequently used gesture. Men showed nonverbal codes 7 times, with the most nonverbal code shown being discomfort. Women showed nonverbal codes 18 times, with the most nonverbal codes shown being discomfort, nervousness, worry, stress and fear, and nervousness. There are 9 nonverbal functions in intergender communication, with repetition being the nonverbal function often shown. Women are more likely to get threats from men. Women use nonverbal communication more often.